2003
DOI: 10.2527/2003.811135x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implant regimens (trenbolone acetate-estradiol administered alone or in combination with zeranol) and vitamin D3 on fresh beef color and quality1

Abstract: In the first oftwo experiments, 123 calf-fed steers were used over a 2-yr period to evaluate the effects of trenbolone acetate (TBA)-based implants administered alone or in combination with zeranol implants on fresh beef muscle quality, color, and physiological maturity of the carcass. Implant treatments decreased (P < 0.05) a* values (d 0 and d 3 of retail display) and b* values (d 0, d 1, and d 3 of retail display) after 14 d of aging. Carcasses from cattle initially implanted with Revalor-S and reimplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
3
24
1
4
Order By: Relevance
“…Foutz et al (1997) compared shear force and percentage of tough steaks coming from cattle receiving a 120 mg of TBA implant vs. those receiving 2 separate doses of a 120 mg of TBA implant and reported no implant effects. Reiling and Johnson (2003) found no difference in shear force when cattle were implanted with 120 mg of TBA vs. those implanted with 2 separate doses of an implant containing 120 mg of TBA each. Means within a row (WBS, sensory juiciness) or an item (sensory tenderness) without a common superscript letter differ (P < 0.05).…”
Section: Palatability Traitsmentioning
confidence: 89%
“…Foutz et al (1997) compared shear force and percentage of tough steaks coming from cattle receiving a 120 mg of TBA implant vs. those receiving 2 separate doses of a 120 mg of TBA implant and reported no implant effects. Reiling and Johnson (2003) found no difference in shear force when cattle were implanted with 120 mg of TBA vs. those implanted with 2 separate doses of an implant containing 120 mg of TBA each. Means within a row (WBS, sensory juiciness) or an item (sensory tenderness) without a common superscript letter differ (P < 0.05).…”
Section: Palatability Traitsmentioning
confidence: 89%
“…et al (1991) 0.12 0.20 Huck et al (1991) 0.23 0.20 Hunt et al (1991) -0.15 0.39 Gerken et al (1995) 0.40 0.25 Samber et al (1996) 0.24 0.10 Foutz et al (1997) 0.32 0.17 Rumsey et al (1999) 0.95 0.33 Pritchard et al (2000) 0.00 0.20 Roeber et al (2000) 0.37 0.11 Barham et al (2003) 0.37 0.11 Platter et al (2003) 0.63 0.19 Reiling & Johnson (2003) WA-1 trial: Thompson et al (2008a) This trial, utilising three cooking methods, covered a wide range of muscles for heifers and steers. The details are covered in full in Thompson et al (2008a).…”
Section: Resultsmentioning
confidence: 99%
“…This may be further evidence that E2 and other oestrogens act on the somatotropic axis to increase hepatic secretion of IGF-I, while TBA and other androgens act through a yet-unidentified mechanism. An increase in bone maturity scores when compared with nonimplanted controls has been associated with oestrogens (Turner et al, 1995), androgens (Moran et al, 1991) and the steroids in combination (Reiling & Johnson, 2003). Until now, however, there has not been a comparative study that evaluates serum IGF-I where treatments included E2 and TBA alone and where those amounts of E2 and TBA were represented exactly in a third combination treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about the impacts of these practices on bone growth and the metabolites that affect bone ageing. The same implantation system increased the percentage ash content of the cartilage of the 9th to 11th thoracic vertebrae and consequently advanced bone maturity scores (Reiling & Johnson, 2003). When implanted with E2 only, Kniffen et al (1999) found a dosage-dependent advancement in epiphyseal plate closure of metacarpal bones III and IV in beef heifers.…”
Section: Introductionmentioning
confidence: 90%